The romantic [compact disc] - Mars, Bruno, 1985- (Atlantic, 2026)
After collaborating with Anderson .Paak as Silk Sonic, Bruno Mars returns with his first solo album since 2016's 24k Magic. His new release includes the single I Just Might.